Ethical Decision Making in Tax Planning with Tri Kaya Parisudha as a Moderating Variable - Gede Fajar Utama; I Gusti Ayu Made Asri Dwija Putri; I Gusti Ayu Nyoman Budiasih; I Gde Ary Wirajaya (Indonesian Journal of Taxation and Accounting, 2026)
Purpose – This study examines the effects of Machiavellian traits, risk preference, information currency, and work experience on tax consultants’ ethical decisions, and the moderating role of Tri Kaya Parisudha, a Balinese Hindu philosophy emphasizing purity of thought, speech, and action. Integrating local cultural values into the Theory of Planned Behavior, this study explains when cultural ethics succeed or fail by distinguishing declarative ethical knowledge from deep behavioural internalisation. Methods – A quantitative explanatory design was used. From 396 tax consultants registered with IKPI in Bali, 191 consultants holding level B or C practice licenses were selected through purposive sampling. Data were collected using a four-point Likert-scale questionnaire and analysed with SEM-PLS using SmartPLS 4.0. Findings – The measurement model met validity and reliability criteria, and the structural model explained 72.0% of the variance in ethical decisions. Machiavellian traits and risk preference negatively affected ethical decisions, while information currency and work experience had positive effects. Contrary to expectations, Tri Kaya Parisudha strengthened the negative effects of Machiavellian traits and risk preference, indicating that declarative cultural ethics may be insufficient to restrain deep-seated personality traits and may even rationalise manipulative behaviour. However, Tri Kaya Parisudha strengthened the positive effects of information currency and work experience. Research implications – Ethics training should move beyond cultural-value transmission toward internalisation through case-based discussion, reflection, and mentoring. Recruitment should also assess Machiavellianism and risk preference. Originality – This study refines TPB by showing the conditional role of local cultural ethics in tax consultants’ ethical decision making.